2022
DOI: 10.1371/journal.pone.0264137
|View full text |Cite
|
Sign up to set email alerts
|

Association between living in municipalities with high crowding conditions and poverty and mortality from COVID-19 in Mexico

Abstract: Background The World Health Organization stated a pandemic by severe acute respiratory syndrome coronavirus SARS-Cov2 (COVID-19) on March, 2020 with devastating implications for populations, healthcare systems, and economies globally. Objective The present study explores the association between patients living in municipalities with crowding conditions and poverty and mortality from COVID-19 in Mexico; specifically evaluating the socioeconomic characteristics of the municipality in which the patients reside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
(51 reference statements)
4
17
0
Order By: Relevance
“…Most patients started treatment after eight weeks, and the relative numbers of this group have continued to increase during the pandemic. Evaluation of this indicator is important in Mexico, as the population most affected by COVID-19-related mortality lives in overpopulated and poor areas ( 50 ) and is also the most affected by CC ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients started treatment after eight weeks, and the relative numbers of this group have continued to increase during the pandemic. Evaluation of this indicator is important in Mexico, as the population most affected by COVID-19-related mortality lives in overpopulated and poor areas ( 50 ) and is also the most affected by CC ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of access to high-complexity healthcare centers and tests that allow prioritization of high-risk cases cause patients to quickly lead to serious conditions or death. Also, the population with a lack of access to public services and with suboptimal housing conditions will be more exposed not only to COVID-19 but also to other infectious diseases, and indeed, to a greater risk of death ( 14 , 31 , 33 35 ). Finally, we observed a gradual reduction in the risk of mortality from COVID-19 from the first wave to the fifth wave, in the highest poverty levels of the CMPI, similar than in the studies by Hussey et al, Leveau et al, and Bastos et al This may be explained by some increase in herd immunity and vaccination efforts in the population ( 32 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inequities in social determinants of health may lead to different unfavorable health outcomes in COVID-19 patients ( 10 – 14 ). Current scientific evidence indicated that the development of severe complications, including death, in COVID-19 patients have been associated with biological, social, and economic factors ( 12 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic vulnerabilities affect the number of COVID-19 cases, mortality, and access to healthcare services or testing32 in distinct places such as Geneva,33 San Francisco34 or Mexico City,35 among others. In Brazil, socioeconomic inequalities disproportionately affected the evolution of the pandemic and the outcome for more vulnerable populations 36.…”
Section: Discussionmentioning
confidence: 99%